ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN INTERAKTIF GOOGLE SITES BERBANTUAN CANVA MATERI PERKALIAN KELAS III SEKOLAH DASAR - Faradisha, Ovi; Mansur, Nabilah; Kamil, Nurdin; Nurani, Dwi Cahaya; Astika, Ruri Tria; Najwa, Wulida Arina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the learning conditions for Mathematics in class III D at SDN 106 Palembang and to identify the need for digital learning media as the basis for developing a Google Sites-based learning platform. The research used observation and interviews with the homeroom teacher. The results indicate that the learning process follows the Merdeka Curriculum; however, its implementation is still dominated by lecture-based methods and conventional learning media. Digital facilities such as projectors and internet access are available but have not been optimally utilized due to unstable electricity. Students show high enthusiasm towards interactive media, although their understanding of multiplication varies. The teacher stated that digital media greatly supports students’ focus and comprehension. These findings highlight that the development of interactive learning media using Google Sites integrated with Canva is highly relevant to support more engaging, varied, and student-centered Mathematics learning.